Architectures of hurry : mobilities, cities and modernity - Dennis, Richard, 1949-; Holdsworth, Deryck, 1947-; Mackintosh, Phillip Gordon, 1960- (Abingdon, Oxon ; New York, NY : Routledge, 2018)
''Hurry' is an intrinsic component of modernity. It exists not only in tandem with modern constructions of mobility, speed, rhythm, and time-space compression, but also with infrastructures, technologies, practices, and emotions associated with the experience of the'mobilizing modern'.'Hurry' is not simply speed. It may result in congestion, slowing-down or inaction in the face of over-stimulus. Speeding-up is often competitive: faster traffic on better roads made it harder for pedestrians to cross, or for horse-drawn vehicles and cyclists to share the carriageway with motorised vehicles. Focussing on the cultural and material manifestations of'hurry', the book's contributors analyse the complexities, tensions and contradictions inherent in the impulse to higher rates of circulation in modernizing cities. The collection includes but also goes beyond accounts of new forms of mobility (bicycles, buses, underground trains) and infrastructure (street layouts and surfaces, business exchanges, and hotels) to show how modernity's'architectures of hurry' have been experienced, represented, and practised since the mid-nineteenth century. Ten case studies explore different expressions of'hurry' across cities and urban regions in Asia, Europe, and North and South America, while substantial introductory and concluding chapters situate'hurry' in the wider context of modernity and mobility studies and reflect on the future of'hurry' in an ever-accelerating world. This diverse collection will be relevant to researchers, scholars and practitioners in the fields of planning, cultural and historical geography, urban history and urban sociology'--
Architectures of hurry: an introductory essay / Richard Dennis, Phillip Gordon Mackintosh, and Deryck W. Holdsworth --'She scorches now and then' : American women and the construction of 1890s cycling / Christina E. Dando -- The London bus : an unlikely architecture of hurry / Richard Dennis -- The tales of two mobility infrastructures : the street and the underground railway of Buenos Aires, 1880s-1940s / Dhan Zunino Singh -- Hurry-slow : automobility in Beijing, or a resurrection of the kingdom of bicycles? / Glen Norcliffe and Boyang Gao -- An architecture of sluggishness : organic infrastructure and anti-mobility in Toronto, 1870-1910 / Phillip Gordon Mackintosh -- Keeping pedestrians in their place : technologies of segregation on the streets of East London / David Rooney -- Hurried exchanges : hybrid office buildings and their uses in the late nineteenth century / Deryck W. Holdsworth -- Shelter from the hurry : hospitality in Montreal, 1836-1913 / Sherry Olson and Mary Anne Poutanen -- Pedestrianism, money and time : mobilities of hurry in George Gissing's the private papers of Henry Ryecroft / Jason Finch --'We're going to move. I can't rush backwards and forwards, I'll go mad. I am sure of it.' Representations of speed and haste in English life writing, 1846-1958 / Colin G. Pooley and Marilyn E. Pooley -- Epilogue : mobilizing hurrysome historical geographies / Phillip Gordon Mackintosh, Deryck W. Holdsworth, and Richard Dennis.
Includes bibliographical references.
Keywords: Urban transportation -- Social aspects